Biochar Co-Applied with Lime Enhances Soil Phosphorus Availability via Microbial and Enzymatic Modulation of Paddy Soil - Yang Zhang; Caidi Yang; Jun Wang; Shenggao Lu (Microorganisms)
Soil microorganisms play a crucial role in improving soil phosphorus (P) availability. However, few studies have explored the changes in microbial community structure and their underlying mechanisms for improving soil P availability with the application of biochar and lime. Three kinds of biochar, made from rice straw (SB), Chinese fir wood sawdust (WB), and pig manure (MB), alone and with lime (SBL, WBL, and MBL), were applied to paddy soil to reveal the biochemical mechanisms for enhancing soil P availability. High-throughput sequencing and real-time PCR were used to investigate soil microbial communities and P functional genes. The three biochars increased the soil’s available P in the order of MB > SB > WB. Biochar co-applied with lime increased the available P (Olsen-P by 169–209%) and inorganic P (Al-P by 53.4–161%, Fe-P by 96.3–198%, and Ca-P by 59.0–154%) more than biochar alone, compared to the control (CK). Both biochar alone and co-applied with lime increased the activities of alkaline phosphomonoesterase (ALP), phosphodiesterase (PD), and inorganic pyrophosphatase (IPP) by 369–806%, 28.4–67.3%, and 37.9–181%, respectively, while it decreased the activity of acidic phosphomonoesterase (ACP) by 15.1–44.0%, compared to CK. Biochar, both alone and co-applied with lime, reduced the copy number of phoC gene by 5.37–88.7%, while it increased the phoD, gcd, and pqqC genes by 51.3–533%, 62.1–275%, and 25.2–158%, respectively, compared to CK. A correlation analysis and partial least squares path modeling (PLS-PM) indicated that Olsen-P, Bray-1 P, and inorganic P were significantly positively correlated with the activities of ALP, PD, IPP, and the phoD gene. Biochar co-applied with lime increased the relative abundances of the phoD-harboring bacteria Proteobacteria, Firmicutes, and Acidobacteria, which promoted the transformation of P to the effective state. Meanwhile, the dominant species Anaerolinea, Ascomycota, Mucoromycota, and Chaetomium provided rich effective nutrients for the soil microorganisms by accelerating the decomposition of soil organic matter, thus promoting phosphatase activity. It could be inferred that the optimized microbial community structure improved phosphatase activity by increasing the phoD gene and available nutrients, thus promoting the soil P availability. Biochar co-applied with lime had a better effect on increasing the P availability and rice yields than biochar alone.